RANCANGAN BALANCED SCORECARD DALAM PENCAPAIAN SASARAN STRATEGIK - Natalia Wijaya; Andry Irwanto (Jurnal Ekonomi dan Bisnis Airlangga, 2020)
Introduction: This study to help the company evaluate the implementation strategies its is intended to design performance measurement using balanced scorecard in a light brick manufacturing company.Methods: This study uses uses qualitative in collecting data methods for designing Balanced ScorecardResults: The results showed that the company had a vision, mission, and strategy in making light bricks but it had not yet been translated into action. In the financial perspective the company driven by strategic goals in the form of increased revenue and cost efficiency. On the perspective of its target customers is the improvement of product quality and customer service as well as the reputation and image of the company. On the internal perspective is production planning, partnerships with suppliers, market and customer service capacity. The learning and growth perspective on implementation of corporate values, development of human resources, and development of an integrated information system is its target.Conclusion and suggestion: Balanced scorecard design is expected to assist companies in implementing it properly.